Pemanfaatan Barang Bekas Menjadi Komposter Anaerobik sebagai Upaya Pengelolaan Sampah Organik di Desa Bluru Kidul, Sidoarjo - Nur Laili Alfiatin Mukharomah; Intan Laili Ni’matul Khoir; Ainun Rahmawati Lukito (Jurnal Kabar Masyarakat, 2024)
Indonesia's population reached 282,477,584 in 2024, presenting significant challenges in waste management, especially in densely populated areas. In Sidoarjo, the waste volume amounts to 598 tons per day, with a recycling rate of only 7-9%. The Kuliah Kerja Nyata Tematik (KKN-T) program in Bluru Kidul village aims to enhance waste management through the promotion of anaerobic composters, which convert organic waste into compost. This community service initiative involves identifying issues, observing conditions, formulating solutions, and educating on the importance of household waste management, particularly organic waste, for producing useful plant fertilizer. This outreach session provided residents of Desa Bluru Kidul with new understanding and skills to utilize used gallon containers as anaerobic composters and organic waste as raw material for oxygen-free compost, thereby supporting Sustainable Development Goal (SDG) 12, which focuses on environmentally conscious consumption and production in villages